Ketogenic diet in civilization diseases - Monika Kusz; Adam Alzubedi; Paweł Polski; Joanna Popiołek; Ewa Kuźma (Journal of Education, Health and Sport, 2018)
The low-carbohydrate ketogenic diet (LCKD) is a high fat and low carbohydrate and low protein diet. It was found to be promising in controlling diabetes mellitus. (DM)., epilepsy, obesity, cardiovascular diseases. Ketogenic diet lowers blood sugar and insulin levels, and shifts the body’s metabolism from carbs and towards fat and ketones.The primary goal of inducing ketosis is to help patients with rare metabolic disorders in a situation where pharmacological treatment was not effective.